2011
DOI: 10.1159/000323010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Carhart Effect in Congenital Middle Ear Malformation with Both an Intact External Ear Canal and a Mobile Stapes Footplate

Abstract: The medical charts of 41 ears with congenital middle ear malformation with both an intact external ear canal and a mobile stapes footplate were reviewed retrospectively to study the Carhart effect. The operations were categorized as successful or unsuccessful according to the extent of decrease in the average air-bone gap. Statistically significant differences were observed between the 2 groups with respect to the changes in pure-tone average and the changes in the bone conduction (BC) threshold at 1 and 2 kHz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 38 publications
4
12
0
Order By: Relevance
“…These results are similar to those found in other studies: PTA improvement varied from 16 to 30 dB and success rate varied from 56 to 70% [Teunissen and Cremers 1993a;Kisilevsky et al, 2009;Sakamoto et al, 2011;Thomeer et al, 2012;Philippon et al, 2013]. Two other studies showed particularly good success rates of 84.6 and 90% and also demonstrated that audiometric results are equivalent, regardless of the type of chain reconstruction surgery performed .…”
Section: Discussionsupporting
confidence: 90%
“…These results are similar to those found in other studies: PTA improvement varied from 16 to 30 dB and success rate varied from 56 to 70% [Teunissen and Cremers 1993a;Kisilevsky et al, 2009;Sakamoto et al, 2011;Thomeer et al, 2012;Philippon et al, 2013]. Two other studies showed particularly good success rates of 84.6 and 90% and also demonstrated that audiometric results are equivalent, regardless of the type of chain reconstruction surgery performed .…”
Section: Discussionsupporting
confidence: 90%
“…Several studies reported achieving significant hearing gains by exploratory tympanotomy and ossiculoplasty in subjects with congenital ossicular anomalies [11,19,22,23]. The rate of successful ABG closure (<20 dB HL) achieved at 6 months postoperation in our study following exploratory tympanotomy and ossiculoplasty, i.e., 87.5%, is comparable to that of previous studies, which reported closure rates ranging from 56% to 70% [11,19,22,23].…”
Section: Postoperative Audiometric Outcomes In Subjects With Second Psupporting
confidence: 83%
“…Several studies reported achieving significant hearing gains by exploratory tympanotomy and ossiculoplasty in subjects with congenital ossicular anomalies [11,19,22,23]. The rate of successful ABG closure (<20 dB HL) achieved at 6 months postoperation in our study following exploratory tympanotomy and ossiculoplasty, i.e., 87.5%, is comparable to that of previous studies, which reported closure rates ranging from 56% to 70% [11,19,22,23]. Although four types of surgery were performed in our cohort (TORP, PORP, IFA, and malleostapedotomy), the small sample size in each group (except for the TORP group) prevented us from determining whether one type was superior to the others.…”
Section: Postoperative Audiometric Outcomes In Subjects With Second Pmentioning
confidence: 99%
“…ABG closure to 10 dB or less was reached in 14% to 29% of the cases in three studies. 3,14,15,17 ABG closure to 20 dB or less was reported in seven studies 3,[12][13][14][15][16][17][18] and was reached in 28% to 95% of the cases. The percentages of ABG closure to within 20 dB found in this study accord well to those described in the literature.…”
Section: Discussionmentioning
confidence: 91%
“…A rapid systematic literature search identified nine articles 3,[11][12][13][14][15][16][17][18] reporting audiometric results following middle ear surgery in children with class III congenital middle ear malformations with a mobile stapes (Table IV). In two of these, 3,17 a large portion of the included cases overlapped.…”
Section: Discussionmentioning
confidence: 99%